Evaluation of the impact of a 3-week specific-sport rehabilitation program on neuromotor control during single-leg countermovement-jump tests in professional soccer players with lower-limb injuries - Geoffrey Memain; Geoffrey Memain; Geoffrey Memain; Christopher Carling; Christopher Carling; Jean Bouvet; Pascal Maille; Bertrand Tamalet; Paul Fourcade; Paul Fourcade; Eric Yiou; Eric Yiou (Frontiers in Sports and Active Living)
PurposeThis study investigated the evolution of neuromotor control during a typical short sport-specific rehabilitation program (SSR) in professional soccer players who had incurred a major lower-limb injury (n = 15, chondral and muscle injuries, ACL-reconstruction).MethodsAll injured participants (n = 15) were in the on-field rehabilitation phase of their specific sport rehabilitation process, prior to return to play. An experimental group (EG, chondral and muscle injuries, ACL-reconstruction) followed a 3-week SSR-program composed of muscular and core strengthening (weightlifting, functional stability, explosivity and mobility exercises), running and cycling, neuromotor reprogramming, cognitive development and specific soccer on-field rehabilitation (acceleration, braking, cutting, dual-contact, high-speed-running, sprint, jump, drills with ball). Neuromotor control via analysis of movement kinematics, muscle activation and kinetic parameters was evaluated using a single-leg Countermovement-Jump, pre- and post- rehabilitation program. A control group (n = 22) of healthy soccer players of similar standards performed the same single-leg Countermovement-Jump to provide reference values regarding the level to be attained by the injured players for return to play.ResultsIn the experimental group, almost all kinetic analyses values progressed during the program and significantly for concentric Rate-of-Force-Development (p < 0.05), height jump (p < 0.001) and Reactive-Strength-Index Modified (p < 0.001) but remained lower than control group values for RSI-Mod (p < 0.05) and RFDconcentricLate (p < 0.001). Activation changed (p < 0.05) for all muscles except for rectus femoris and medial gastrocnemius in the pushing phase and rectus femoris during landing in the EG. Activation of all muscles decreased for EG, except for semitendinous which increased. Regarding kinematic analyses during the landing phase, there were a significant decrease in peak trunk flexion (p < 0.001) and lateroflexion (p < 0.001) and an increase in peak knee flexion (p < 0.001) for both legs. Trunk flexion (p < 0.001) and lateroflexion (p < 0.001) values were again higher for EG while knee flexion remained significantly lower than the CG (p < 0.001).ConclusionThe SSR generally improved neuromotor control suggesting that the present specific sport rehabilitation program, albeit of only three weeks duration, was effective in aiding elite footballers recover their neuromotor qualities although this was potentially insufficient to return to the values observed in healthy players.